Correlation between timing of surgery and post-operative outcome in traumatic acute subdural hematoma - Huda, M. Shamsul; Sarker, Asit Chandra; Siddica, Ayesha (International Journal of Research in Medical Sciences, 2024)
Background: The timing of surgery in acute subdural hematoma affects post-operative outcomes and is a modifiable factor, along with other variables, impacting patient prognosis following surgical intervention. Methods: A prospective observational study was conducted at department of neurosurgery, Dhaka Medical College Hospital from March 2020 to August 2021. Total 64 patients were included in this study. Data were collected by using preformed data collection sheet. Timing of surgery of all patients documented. Outcome was measured according to the Glasgow outcome scale (GOS) at discharge and at one month following surgery. Statistical analysis was performed by SPSS (version 25). To determine correlation, Spearman’s correlation coefficient test was done. Result was considered significant when p value <0.05. Results: Most of the patients were adult with mean age 48.3±10.6 years. Male were predominant (76%). Majority of cases (67%) were operated within 4-24 hours of injury. Overall mortality was 32.8% and favorable outcome (GOS 4, 5) was 39%. The time from injury to operative evacuation of the acute subdural hematoma in regards of outcome, such as morbidity and mortality, had statistically significant negative correlation. Significant negative correlation was also found between timing of surgery and post-operative Glasgow coma scale. Conclusions: Significant negative correlation was found in terms of GOS with timing of surgery, which had potential influence on post-operative GCS of patients of ASDH who were operated. It was seemed that early surgery may improve post- operative GCS and GOS.